Neuromyelitis optica and neuromyelitis optica spectrum disorders: The evaluation of 86 patients followed by Istanbul Bilim University, department of neurology - Altunrende, Burcu; Tavlı, Ahmet Mithat; Altınkaya, Ayça; Topçular, Barış; Kocarslan, Meryem; Server, Sadık; Fırtına, Sinem; Yenice, Sedef; Akman Demir, Gülsen (Sage PubLlications, 2015)
Background and objectives: Neuromyelitis optica (NMO) and its spectrum disorders (NMOSD) are relatively rare disorders. We aimed to evaluate clinical characteristics and disease course of the NMOSD patients followed at our department. Patients and methods: All the patients with the diagnosis of NMO/ NMOSD followed since the establishment of our multipl sclerosis clinic in April 2011, were evaluated. Results: There were 86 patients (66 female, 20 male) with NMO/ NMOSD followed at our MS unit; 24 had NMO, 42 had recurrent optic neuritis (RON); and 20 had longitudinally extensive transverse myelitis (LETM). The disease course was relapsing in 70 patients e296 Abstracts / Journal of the Neurological Sciences 357 (2015) e295–e323 (81%). The first attack was bilateral ON (BON) and TM in 3 patients, ON and TM in 1 patient, ON in 50 patients (bilateral in 6) and TM in 26 patients. NMO IgG was positive in 12 patients with NMO (55%), 4 patients with LETM (25%), and 8 patients with RON (25%). Oligoclonal band was positive in 15 out of 44 patients (34%). In NMO/NMOSD patients, cranial magnetic resonance imaging (MRI) showed no abnormality in 48; nonspecific lesions in 37; and 1 patient had hypothalamic lesion. In spinal MRIs, 41 patients had LETM; six had suspected hyperintense T2 lesion in C5. Conclusion: This is one of the largest single center series collected over 4 years. NMO/NMOSD seems to be over-represented in our center since it is one of the few where NMO IgG testing is available. In NMO/NMOSD, early diagnosis and treatment is important to prevent the patient from the permanent disability.
WOS: 000354258600097
Keywords: Transient Hepatic Attenuation Differences; Superior Vena Cava